Group Decision Making for Hazard Analysis and Consequence Modelling Software Selection with AHP - Saliha Çetinyokuş; Emre Çalışkan; Erdem Aksakal; Tahsin Çetinyokuş (Iranian Journal of Chemistry & Chemical Engineering, 2020)
Software evaluation and selection have begun to be addressed as a topic title along with the fact that microcomputers and then personal computers have become widespread and have been used in the operations of businesses. In this study, it was focused on the selection of software for identifying the physical effect distances of the explosion, fire, and toxic emission, which is an important need for industrial institutions containing, using or storing hazardous chemicals. The evaluation and selection of software for the Hazard Analysis and Consequence Modeling (HACM) of potential accidents was studied at first. In means of methodology, questionnaires consisting of original questions were applied to the experts. The results obtained from questionnaires according to the Likert scale, were converted into Analytical Hierarchy Process (AHP) suggestion matrices. In this way, the inconsistency problem in the pairwise comparison matrices was eliminated. As a result, evaluation and selection were made among the HACM software.